The Last Mountain Man : Vengeance of the Mountain Man - Book 19 - Johnstone, William W. (New York, NY : Pinnacle Books, Kensington Publishing Corp., 2016)
After years on the run, Sundance, a vicious, vengeful gunfighter, brings together a fearsome gang of cutthroats and sets out for the Sugarloaf, with the intention of seeking revenge on mountain man Smoke Jensen.
Keywords: Jensen, Smoke; Fiction; Western fiction